Expression of DEP Domain-Containing 1B in Canine Lymphoma and Other Types of Canine Tumours. (May 2021) - Morinaga, Yuki; Igase, Masaya; Yanase, Takuma; Sakai, Yusuke; Sakai, Hiroki; Fujiwara-Igarashi, Aki; Tsujimoto, Hajime; Okuda, Masaru; Mizuno, Takuya
Summary: Canine lymphoma is the most common haematological malignancy in dogs and is typically treated with multidrug chemotherapy. Most cases are at risk of relapse after several courses of chemotherapy and the oncogenic mechanism remains unknown. This study was aimed at identifying genes expressed in canine lymphoma by cDNA microarray. We found elevated expression of Dishevelled, EGL-10 and pleckstrin (DEP) domain-containing 1B ( DEPDC1B ) in canine lymphoma cells compared with cells and tissues from healthy dogs. Canine DEPDC1B protein was detected in 13 of 41 lymphoma specimens by immunohistochemistry, but was not detected in lymph nodes from normal dogs. Immunoreactive DEPDC1B protein was also detected in several other types of canine tumour. This is the first report documenting the association of DEPDC1B with canine cancer and the results suggest that DEPDC1B might serve as a potential marker or therapeutic target for canine malignancies.